2019
DOI: 10.1177/1747021819881622
|View full text |Cite
|
Sign up to set email alerts
|

Visual working memory load does not affect the overall stimulus processing time in visual search

Abstract: The dual-task paradigm is widely used in studying the interaction between visual search and working memory. A number of studies showed that holding items in working memory delays the overall response time (RT) in visual search, but it does not affect the efficiency of search (i.e., the slope of the RT × set size function). Why the memory load merely affects the overall RT? Some researchers proposed that this load-effect on overall RT may be caused by factors that only affect response selection processes, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A dual-task paradigm is often used to examine the interaction between two distinct mental mechanisms, such as the interaction between attention and WM (e.g., Woodman et al, 2001; Xin & Li, 2020), and the interaction between spatial WM and visual WM (e.g., Sanada et al, 2015; Wood, 2011). However, because attention is involved in the maintenance of WM (Barrouillet et al, 2011; Cowan, 2005), when dual-task cost in capacity is observed in a WM task it is often difficult to tell whether the dual-task cost is due to interference from executive processes or from nonexecutive processes (such as interference across WM representations).…”
Section: Discussionmentioning
confidence: 99%
“…A dual-task paradigm is often used to examine the interaction between two distinct mental mechanisms, such as the interaction between attention and WM (e.g., Woodman et al, 2001; Xin & Li, 2020), and the interaction between spatial WM and visual WM (e.g., Sanada et al, 2015; Wood, 2011). However, because attention is involved in the maintenance of WM (Barrouillet et al, 2011; Cowan, 2005), when dual-task cost in capacity is observed in a WM task it is often difficult to tell whether the dual-task cost is due to interference from executive processes or from nonexecutive processes (such as interference across WM representations).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, additional experiments in which the eye movements are monitored during search are necessary to further investigate these diverging effects of WM load on search performance and search efficiency. A further explanation for this inconsistency regarding the different effect of spatial WM load on search performance and search efficiency was recently provided by Xin and Li (2020). They argued that the increased extent of executive control to maintain a (non-spatial) WM load might decrease the participants' confidence level such that the observed response time differences are mainly due to the stage of response selection.…”
Section: Discussionmentioning
confidence: 99%